2021
DOI: 10.1002/jmri.27589
|View full text |Cite
|
Sign up to set email alerts
|

Bowel Wall Visualization Using MR Enterography in Relationship to Bowel Lumen Contents and Patient Demographics

Abstract: Background MR enterography (MRE) is generally performed without bowel preparation, but the frequency and extent by which bowel contents affect bowel wall visualization are poorly described in the literature. Purpose To evaluate MRE bowel wall visualization quality relative to bowel lumen contents and patient demographics. Study Type Retrospective, single‐center. Population One hundred and four consecutive patients (mean age 29 years, range 5–76 years) without prior bowel resection who had undergone MRE. Field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The lack of an accurate noninvasive diagnostic test restricts patient management, therapy monitoring and stratification in clinical trials. Noninvasive surrogate markers are warranted to replace invasive diagnostic procedures 5–7 …”
mentioning
confidence: 99%
“…The lack of an accurate noninvasive diagnostic test restricts patient management, therapy monitoring and stratification in clinical trials. Noninvasive surrogate markers are warranted to replace invasive diagnostic procedures 5–7 …”
mentioning
confidence: 99%
“…This may be of concern for patients undergoing MRE who have IBD, which primarily affects the colon 8 . Zhang et al 7 also reported that air‐containing bowel in the colon compromised the bowel wall visualization in small bowel regions, particularly in children, which is contrary to the findings from Sinha et al 6 Moreover, Crohn's disease affects the colon of 56% of pediatric patients compared to 23% of adult patients with penetrating disease 9 . Thus, to minimize image misinterpretations based on colon content, Zhang et al suggest that bowel cleansing may be appropriate prior to MRE for patients where colonic involvement might be of concern 7 …”
mentioning
confidence: 99%
“…6 In this issue of JMRI, a research article by Zhang et al explored bowel wall visualization using MRE in relation to the bowel lumen content. 7 They conducted a retrospective study in a cohort of adult and pediatric patients who underwent MRE without any bowel cleansing preparation. GI radiologists reviewed the images (T2-weighted images and T1-weighted images with and without gadolinium) and assessed the bowel lumen content, and graded the degree of bowel distension and quality of wall enhancement for different segments of the intestinal tract.…”
mentioning
confidence: 99%
See 2 more Smart Citations